2022
DOI: 10.1128/jb.00108-22
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of the LexA-Mediated DNA Damage Response in Streptomyces venezuelae

Abstract: The transcriptional regulator LexA functions as a repressor of the bacterial SOS response, which is induced under DNA-damaging conditions. This results in the expression of genes important for survival and adaptation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…The SOS response is classically associated with the activation of prophages, and has recently been described in S. venezuelae (48). In S. ambofaciens ATCC 23877, transcripts of the key actors of the SOS response such as RecA, LexA, RecN, DnaE, RuvA Holliday junction DNA helicase (48) were not up-regulated in the ‘HT’ condition compared to the ‘MM’ reference ( Table S5 ). This result suggests that the SOS response is not involved in the induction of Samy production in the ‘HT’ condition, or may be so transient and/or only present in part of the cell population that it was not detected by our bulk transcriptome analysis.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The SOS response is classically associated with the activation of prophages, and has recently been described in S. venezuelae (48). In S. ambofaciens ATCC 23877, transcripts of the key actors of the SOS response such as RecA, LexA, RecN, DnaE, RuvA Holliday junction DNA helicase (48) were not up-regulated in the ‘HT’ condition compared to the ‘MM’ reference ( Table S5 ). This result suggests that the SOS response is not involved in the induction of Samy production in the ‘HT’ condition, or may be so transient and/or only present in part of the cell population that it was not detected by our bulk transcriptome analysis.…”
Section: Resultsmentioning
confidence: 98%
“…The SOS response is classically associated with the activation of prophages, and has recently been described in S. venezuelae (48). In S. ambofaciens ATCC 23877, transcripts of the key actors of the SOS response such as RecA, LexA, RecN, DnaE, RuvA Holliday junction DNA helicase (48) were not up-regulated in the ‘HT’ condition compared to the ‘MM’ reference ( Table S5 ).…”
Section: Resultsmentioning
confidence: 98%
“…The TD variant is thus characterized by a massive loss of MGEs. This could result from a severe state of oxidative stress, because oxidative DNA damages are known to favor the excision of MGEs through the induction of the SOS stress response [ 28 , 29 ]. The loss of MGEs may give the TD variant a greater genomic stability than its parental strain.…”
Section: Resultsmentioning
confidence: 99%
“…However, a most important question is what could have been the initial triggering event responsible for the high genetic instability of the TD variant. Because the excision of MGE is known to be provoked by oxidative stress [ 28 , 29 ], it might be the deletion of the arseno polyketide pathway that would be responsible for the severe raise in oxidative stress leading to high genetic instability. This genetic instability would have selected events promoting the storage of acetyl-CoA as lipids to reduce the activation of the oxidative metabolism and thus the generation of oxidative stress [ 4 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, they did not provide experimental evidence for this claim. Second, Schlimpert and co-workers used a lexA deletion mutant of Streptomyces venezuelae to determine the genes under the control of the SOS response (Stratton et al, 2022 ). Interestingly, they found that secondary metabolism genes were among the SOS-regulon, in addition to the expected DNA damage repair genes.…”
Section: Introductionmentioning
confidence: 99%